Impact of Bead-Beating Intensity on the Genus- and Species-Level Characterization of the Gut Microbiome Using Amplicon and Complete 16S rRNA Gene Sequencing - Zhang, Bo; Brock, Matthew; Arana, Carlos; Dende, Chaitanya; van Oers, Nicolai Stanislas; Hooper, Lora V.; Raj, Prithvi (Frontiers in Cellular and Infection Microbiology, 2021)
Bead-beating within a DNA extraction protocol is critical for complete microbial cell lysis and accurate assessment of the abundance and composition of the microbiome. While the impact of bead-beating on the recovery of OTUs at the phylum and class level have been studied, its influence on species-level microbiome recovery is not clear. Recent advances in sequencing technology has allowed species-level resolution of the microbiome using full length 16S rRNA gene sequencing instead of smaller amplicons that only capture a few hypervariable regions of the gene. We sequenced the v3-v4 hypervariable region as well as the full length 16S rRNA gene in mouse and human stool samples and discovered major clusters of gut bacteria that exhibit different levels of sensitivity to bead-beating treatment. Full length 16S rRNA gene sequencing unraveled vast species diversity in the mouse and human gut microbiome and enabled characterization of several unclassified OTUs in amplicon data. Many species of major gut commensals such as Bacteroides, Lactobacillus, Blautia, Clostridium, Escherichia, Roseburia, Helicobacter, and Ruminococcus were identified. Interestingly, v3-v4 amplicon data classified about 50% of Ruminococcus reads as Ruminococcus gnavus species which showed maximum abundance in a 9 min beaten sample. However, the remaining 50% of reads could not be assigned to any species. Full length 16S rRNA gene sequencing data showed that the majority of the unclassified reads were Ruminococcus albus species which unlike R. gnavus showed maximum recovery in the unbeaten sample instead. Furthermore, we found that the Blautia hominis and Streptococcus parasanguinis species were differently sensitive to bead-beating treatment than the rest of the species in these genera. Thus, the present study demonstrates species level variations in sensitivity to bead-beating treatment that could only be resolved with full length 16S rRNA sequencing. This study identifies species of common gut commensals and potential pathogens that require minimum (0-1 min) or extensive (4-9 min) bead-beating for their maximal recovery.